An overview of mercury emission sources and application of activated carbon for mercury removal from flue gas / Hidayu Abdul Rani ... [et al.] - Abdul Rani, Hidayu; Mohamad, Nor Fadilah; Ali, Sherif Abdulbari; Matali, Sharmeela; Sheikh Abdul Kadir, Sharifah Aishah (Research Management Institute (RMI), 2013)
Mercury emission into the atmosphere is a global concern due to its detrimental effects on human health in general. The two main sources of mercury emission are natural sources and anthropogenic sources. Mercury emission from natural sources include volcanic activity, weathering of rocks, water movement and biological processes which are obviously inevitable. The anthropogenic sources of mercury emission are from coal combustion, cement production and waste incineration. Thus, in order to reduce mercury emission it is appropriate to investigate how mercury is released from the anthropogenic sources and consequently the mercury removal technology that can be implemented in order to reduce mercury emission into the atmosphere. Many alternatives have been developed to reduce mercury emission and the recent application of activated carbon showed high potential in the adsorption of elemental mercury. This paper discusses the ability of activated carbon and variable parameters that influence mercury removal efficiency in flue gas.